Development of Five-Tier Diagnostic Test to Identify Misconception in Rigid Body Equilibrium - Uci Fatonah; Maison Maison; M Hidayat (Universitas Lambung Mangkurat, 2022)
The misconception is the interpretation of a concept that is not following the conception agreed upon by scientists. The purpose of the research was to determine the product development process of the five-tier diagnostic test and the product quality of the five-tier diagnostic test. The type of research used is Research and Development (R&D). The development model used is the 4D model. The research sample was 98 students of class XI MIPA 1, XI MIPA 2, XI MIPA 3 and XI MIPA 4 at Senior High School 1 Jambi City. The results showed that the quality of the instrument was feasible to use because the test showed valid qualitative and quantitative results.